2016
DOI: 10.5194/isprs-annals-iv-2-w1-137-2016
|View full text |Cite
|
Sign up to set email alerts
|

A Citygml Extension for Handling Very Large Tins

Abstract: ABSTRACT:In addition to buildings, the terrain forms an important part of a 3D city model. Although in GIS terrains are usually represented with 2D grids, TINs are also increasingly being used in practice. One example is 3DTOP10NL, the 3D city model covering the whole of the Netherlands, which stores the relief with a constrained TIN containing more than 1 billion triangles. Due to the massive size of such datasets, the main problem that arises is: how to efficiently store and maintain them? While CityGML supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…Simple Feature representation for a triangle in ISO 19136:2007 implementation standard GML (Kumar et al, ). The first vertex ( x1, y1, z1 ) of every triangle is repeated as the last vertex ( x1, y1, z1 ) to close the linear ring…”
Section: State‐of‐the‐art In Modeling Terrains With Tinsmentioning
confidence: 99%
See 4 more Smart Citations
“…Simple Feature representation for a triangle in ISO 19136:2007 implementation standard GML (Kumar et al, ). The first vertex ( x1, y1, z1 ) of every triangle is repeated as the last vertex ( x1, y1, z1 ) to close the linear ring…”
Section: State‐of‐the‐art In Modeling Terrains With Tinsmentioning
confidence: 99%
“…We plan to use 3DCityDB (https://www.3dcitydb.org/) (PostgreSQL) for the database implementation of the ADE. Our previous tests have shown that it takes a significantly larger amount of time to populate and index the TIN datasets with the Simple Feature structure than the index‐based data structures in the database (Kumar et al, ). In the case of the ADE, we expect that the loading time from the CityGML ADE file to the database will most likely improve.…”
Section: Conclusion and Further Researchmentioning
confidence: 99%
See 3 more Smart Citations